Patient and public involvement in medical performance processes: A systematic review. (11th December 2018) - Lalani, Mirza; Baines, Rebecca; Bryce, Marie; Marshall, Martin; Mead, Sol; Barasi, Stephen; Archer, Julian; Regan de Bere, Samantha
Abstract: Background: Patient and public involvement (PPI) continues to develop as a central policy agenda in health care. The patient voice is seen as relevant, informative and can drive service improvement. However, critical exploration of PPI's role within monitoring and informing medical performance processes remains limited. Objective: To explore and evaluate the contribution of PPI in medical performance processes to understand its extent, purpose and process. Search strategy: The electronic databases PubMed, PsycINFO and Google Scholar were systematically searched for studies published between 2004 and 2018. Inclusion criteria: Studies involving doctors and patients and all forms of patient input (eg, patient feedback) associated with medical performance were included. Data extraction and synthesis: Using an inductive approach to analysis and synthesis, a coding framework was developed which was structured around three key themes: issues that shape PPI in medical performance processes; mechanisms for PPI; and the potential impacts of PPI on medical performance processes. Main results: From 4772 studies, 48 articles (from 10 countries) met the inclusion criteria. Findings suggest that the extent of PPI in medical performance processes globally is highly variable and is primarily achieved through providing patient feedback or complaints. The emerging evidence suggests that PPI can encourage improvements in the quality of patient care, enable professional development and promote professionalism. Discussion and conclusions: Developing more innovative methods of PPI beyond patient feedback and complaints may help revolutionize the practice of PPI into a collaborative partnership, facilitating the development of proactive relationships between the medical profession, patients and the public.